Executive Committee Minutes 2011-09-22 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 9/8/11 approved. President Report. Statewide Senator Report. Change of name and timeline for Gender and Sexual Health Stakeholder's Exploratory Workgroup approved for Senate agenda. Question from FSAC re: revising (Student Evaluation of Teaching Effectiveness instrument) SETEs. Associated Students Report. SAC Report. Spring University Retreat. Senate agenda approved. Good of the Order.